Trends of inequities in healthcare seeking behavior for diarrhea, fever, and ARI symptoms among women in reproductive age groups for their under-five children in Ethiopian: A multilevel Analysis of EDHS Surveys from 2000 to 2016 - Hailu Fekadu; Wubegzier Mekonnen; Aynalem Adugna; Helmut Kloos; Damen Hailemariam (PLoS ONE, 2025)
Background Ethiopia is one of the developing countries with the highest inequity in the healthcare seeking behavior for under-five children. Despite this fact, not much is known about the trend of inequity, in healthcare seeking-behavior for symptoms of diarrhea, fever and acute respiratory infections (ARIs) among under-five children. Objective This study aimed to measure trends of inequity in healthcare seeking -behavior for diarrhea, fever, and ARI symptoms and its determinant factors among under-five children in Ethiopia. Methods Data from 2000, 2005, 2011, and 2016 Ethiopian Demographic and Health Surveys (EDHSs) were analyzed using the 2019 updated version of the WHO’s Health Equity Assessment Toolkit (HEAT) software. Five equity dimensions were used to disaggregate datasets on healthcare seeking behavior for diarrhea, fever, and ARI symptoms: Based on wealth status, education, place of residence, sex of the child and administrative regions. Second, summary measures such as: equity gaps, equity ratios, population attributable fraction (PAF), population attributable Risk (PAR), absolute concentration index (ACI) and relative concentration index (RCI), was used. The concentration curve and horizontal inequity indices were used to evaluate the wealth-related disparities. To measure the determinants a multilevel logistic regression with 95% confidence interval was employed. Result This study showed remarkable improvement in healthcare seeking behavior for symptoms of diarrhea, fever and ARI among under-five children between 2000 and 2016. The increases are more, from the poorest subgroups compared to the wealthiest. The absolute percentage point changes (or healthcare seeking rate changes) between 2000 and 2016 among the poorest quintile of households are at least twice that of the wealthiest quintile for symptoms of diarrhea. However, significant disparities between the rich and the poor persist for the majority of the indicators examined for the three childhood morbidities. Moreover, horizontal inequity indices and the concentration curve both point out to the existence of pro-rich inequity in healthcare seeking behavior for under five children. In the multilevel analysis various demographic, parental and household characteristic show an association with healthcare seeking behavior for symptoms of diarrhea, fever and ARIs. Conclusion A promising trend is observed in healthcare seeking behavior for diarrhea, fever and ARI symptoms among under-five children. Faster progress in use of healthcare services among the poor than the wealthy in Ethiopia would potentially result in elimination of inequities and rapid improvement in health among the poor. Intervention programs that focused on the underprivileged, while also taking into account the wealthier sub-groups.